Prognostic Value of Serum HE4 Levels and Risk of Ovarian Malignancy Algorithm Scores at the Time of Ovarian Cancer Diagnosis. Issue 7 (1st September 2014) - Kaijser, Jeroen; Van Belle, Vanya; Van Gorp, Toon; Sayasneh, Ahmad; Vergote, Ignace; Bourne, Tom; Van Calster, Ben; Timmerman, Dirk
Abstract : Objectives: The aim of this study is to assess whether the pretreatment serum HE4 levels or the Risk of Ovarian Malignancy Algorithm (ROMA) scores at the time of initial diagnosis are associated with progression-free survival (PFS) and disease-specific survival (DSS) in patients with ovarian cancer receiving either primary debulking surgery or neoadjuvant chemotherapy followed by interval debulking surgery. Methods: A survival analysis of 101 cases of invasive ovarian cancer recruited in a previous diagnostic accuracy study was conducted from 2005 to 2009 at the University Hospital KU Leuven, Belgium. Serum HE4 levels (pM) and ROMA scores (%) were obtained before primary treatment. Dates of death were obtained by record linkage with patient hospital files. Progression was evaluated according to the Response Evaluation Criteria in Solid Tumors. Adjusted hazards ratios (HRs) were estimated using multivariable Cox regression. Results: Eighty patients (79%) with invasive ovarian cancer underwent primary debulking surgery, whereas 21 (21%) received neoadjuvant chemotherapy. The median DSS was 3.72 years (95% confidence interval [CI], 3.19–4.07). Fifty-two patients (51%) died of disease, and 74 patients (73%) had progressive disease during follow-up. On univariable analysis, elevated pretreatment HE4 levels and ROMA scores were related to worse prognosis. However, after the adjustment for classic prognostic variables, HE4 levels (log2-transformed) and ROMA scores were unrelated to DSS (log-2 HE4: adjusted HR, 1.01; 95% CI, 0.84–1.21 and ROMA: adjusted HR per 10% increase, 0.96; 95% CI, 0.84–1.12) and PFS (log-2 HE4: adjusted HR, 0.98; 95% CI, 0.84–1.13 and ROMA: adjusted HR per 10% increase, 0.98; 95% CI, 0.88–1.11). Conclusions: Pretreatment HE4 levels and ROMA scores are not independent prognostic factors for DSS and PFS after multivariable adjustment in patients with ovarian cancer.